Rewiring of the Jasmonate Signaling Pathway in Arabidopsis during Insect Herbivory - Verhage, Adriaan; Vlaardingerbroek, Ido; Raaijmakers, Ciska; Van Dam, Nicole; Dicke, Marcel; Van Wees, Saskia C.; Pieterse, Corné M. (Frontiers in Plant Science, 2011)
Plant defenses against insect herbivores and necrotrophic pathogens are differentially regulated by different branches of the jasmonic acid (JA) signaling pathway. In Arabidopsis, the basic helix-loop-helix leucine zipper transcription factor MYC2 and the APETALA2/ETHYLENE RESPONSE FACTOR (AP2/ERF) domain transcription factor ORA59 antagonistically control these distinct branches of the JA pathway. Feeding by larvae of the specialist insect herbivore Pieris rapae activated MYC2 transcription and stimulated expression of the MYC2-branch marker gene VSP2, while it suppressed transcription of ORA59 and the ERF-branch marker gene PDF1.2. Mutant jin1 and jar1-1 plants, which are impaired in the MYC2-branch of the JA pathway, displayed a strongly enhanced expression of both ORA59 and PDF1.2 upon herbivory, indicating that in wild-type plants the MYC2-branch is prioritized over the ERF-branch during insect feeding. In a two-choice setup the larvae consistently preferred jin1 and jar1-1 plants, in which the ERF-branch was activated, over wild-type Col-0 plants, in which the MYC2-branch was induced. In MYC2- and ORA59-impaired jin1 1/RNAi-ORA59 plants this preference was lost, while in ORA59-overexpressing 35S:ORA59 plants it was gained, suggesting that the herbivores were stimulated to feed from plants that expressed the ERF-branch rather than that they were deterred by plants that expressed the MYC2-branch. The feeding preference of P. rapae could not be linked to changes in glucosinolate levels. Interestingly, application of larval oral secretion into wounded leaf tissue stimulated the ERF-branch of the JA pathway, suggesting that compounds in the oral secretion have the potential to manipulate the plant response toward the caterpillar-preferred ERF-regulated branch of the JA response. Our results suggest that by activating the MYC2-branch of the JA pathway, plants prevent stimulation of the ERF-branch by the herbivore, thereby becoming less attractive to the attacker.